An integrated AHP and VIKOR for design concept evaluation based on rough number. Issue 3 (August 2015) - Zhu, Guo-Niu; Hu, Jie; Qi, Jin; Gu, Chao-Chen; Peng, Ying-Hong
Highlights An integrated rough number based method is presented to evaluate design concepts under subjective environment. Rough number is introduced to deal with the vagueness in decision-making. A novel AHP based on rough number is presented to determine the weight of each evaluation criterion. A rough number based VIKOR is proposed to evaluate the design concept alternatives. The proposed method can effectively enhance the objectivity in design concept evaluation.